Forest Fire Effects on Soil Properties - Elakiya N.; Keerthana G.; Safiya S. (Research Advances and Challenges in Agricultural Sciences Vol. 8, 2024)
The present study highlights forest fire effects on soil properties. One of the most harmful challenges to our forest is fire. Forest fires may have an impact on a combination of vegetation cover, structure, composition, density, and productivity leading to deforestation, population decline, consequences of the forest edge, and exotic animal immigration species. The impact of forest fires on soil physical properties had an emphasis on texture, bulk density, porosity, aggregate stability, and water content and repellency. Following the fire, the surface soil of the burned region had higher soil pH, total nitrogen, accessible phosphorus, potassium, calcium, and magnesium levels than the unburned area. Because of the low fire intensity, the organic matter in the soil and the litter burned, increasing the amount of nutrients available and encouraging the growth of the post-fire community and herb regeneration. Higher-intensity fires totally burn out secondary minerals like magnesium and micronutrients like manganese at extremely high temperatures. They also volatilize nitrogen, phosphate, and potassium in the soil and kill microorganisms. Some nutrients were more readily available by the burning of soil organic matter (OM), such as N, P, and S, while others were volatilized. Controlled fire did not result in any significant changes to the nutrients or physico-chemical composition of soil and can be utilized as an efficient management technique to reduce the harm caused by wildfires to soil. Remote sensing and GIS technology are the highly advanced tools used to detect forest fires, calculate burned areas and determine of changes in land use. As a tool for predicting fires, remote sensing, and GIS are highly essential. Hence it is important to understand how fire affects the physical, chemical, and biological aspects of forest ecosystems.